PENGARUH KEMASAN MODERN DALAM MENINGKATKAN PENDAPATAN POKLAHSAR ABON IKAN LELE (Clarias sp.) DI KECAMATAN CIBINONG KABUPATEN BOGOR - Aprilia, Egi Dita; Yuniarti, Tatty; Sobariah, Sobariah (Marinade, 2021)
The economy is disrupted during the pandemic, especially in micro-businesses, to be able to compete with other companies with fluctuating market conditions, companies must think hard to develop a good marketing strategy. The company's strategy to compete in the business world is to pay attention to the packaging design used. This study aims to increase revenue through the application of modern new product packaging in sales. The study lasted for 3 months starting from March 8 to June 5, 2021 in Cibinong District, Bogor Regency. Parameters analyzed in the form of aspects of knowledge attitude, attitude, and adoption of innovation as well as the application of counseling using pre-test and post-test questionnaires. The results of the research conducted at the knowledge aspect evaluation stage were 43% at Poklahsar Mina Sejahtera and 33% at Poklahsar Panghegar Raya Lestari, an increase in the attitude aspect was 15% at Poklahsar Mina Sejahtera and 4% at Poklahsar Panghegar Raya Lestari, as for the adoption of innovations obtained From the results of the weekly observations of the two Poklahsars, it can be concluded that Poklahsar Mina Sejahtera and Panghegar Raya Lestari have implemented the demonstration results of modern product labels and packaging starting from the 9th week to the 12th week (last week). Sales of products using new packaging and labels were 83 packs for Poklahsar Mina Sejahtera and 64 packs for Poklahsar Panghegar Raya Lestari with an income of Rp. 1.411,000 with a profit of Rp. 278,778 for Poklahsar Mina Prosperous while for Poklahsar Panghegar Raya Lestari, an income of Rp. 1,280,000 with a profit of IDR 297,128.